Romans, rubbish, and refuse : the archaeobotanical assemblage of Regione VI, Insula I, Pompei - Murphy, Charlene Alexandria (Archaeopress Roman archaeology, 2015)
The extensive excavations (1995-2006) by the Anglo-American Project in Pompeii provided a rare insight into chronological change within the city. This research was significant as an insula block within Pompeii had never previously been excavated in its entirety. The analysis of all the recovered seeds, fruits and cereal remains provided an opportunity to undertake a diachronic study of urban Roman plant food consumption and discards, the results of which are discussed here.